The relationship of physical activity and the quality of life in the elderly population: analysis of the brazilian scientific production - Douglas Prado Araújo; Stela Lopes Soares; Diogo Queiroz Allen Palácio (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2018)
It is an integrative review with the objective of analyzing the Brazilian scientific production on the influence of physical activity on the quality of life of the elderly. Articles published in different databases were selected, with descriptors: "Exercise", "Quality of Life", "Elderly", "Elderly aged 80 years and over". As criteria: full text available, in English, old age limit. The Southeast has most of the national production and most of them have a quantitative approach. The scarce and recent scientific production on the subject was also evidenced, which contrasts with the expansion of this population's access to physical practices and physical activity.